Freedom of religion under bills of rights - Babie, Paul, 1966-; Rochow, Neville (Open Access e-Books, 2012)
'The Australian Constitution contains no guarantee of freedom of religion or freedom of conscience. Indeed, it contains very few provisions dealing with rights - in essence, it is a Constitution that confines itself mainly to prescribing a framework for federal government, setting out the various powers of government and limiting them as between federal and state governments and the three branches of government without attempting to define the rights of citizens except in minor respects. ... Whether Australia should have a national bill of rights has been a controversial issue for quite some time. This is despite the fact that Australia has acceded to the ICCPR, as well as the First Optional Protocol to the ICCPR, thereby accepting an international obligation to bring Australian law into line with the ICCPR, an obligation that Australia has not discharged. Australia is the only country in the Western world without a national bill of rights.4 The chapters that follow in this book debate the situation in Australia and in various other Western jurisdictions."--Foreword by The Hon Sir Anthony Mason AC KBE: Human Rights and Courts